Cognitive Resources of New Economy - Khaustova Viktoriia Ye. (PH "INZHEK", 2021)
Global experience shows that society has to be focused on the model of new economy and recommendations of cognitology to improve the reliability of the functioning and development of society. Although many publications partially suggest options for solving this problem, complex analysis of the resources for the development of Ukrainian society still lacks methodological and practical substantiation. Thus, this article is aimed at summarizing the prerequisites for the development of theoretical and practical support for the formation of a social pattern within the new economy alongside with the development and utilization of cognitive resources. The article presents analysis of a) the trend to change social patterns, and b) factors that ensure the switch to using new knowledge that can provide designing and implementing successful reforms of society, as a whole and its economic system, in particular. The article proposes a variant of a collective survey hypothesis: “In a steady growth of the role and value of the latest knowledge in the innovative development of the economy, the cognitive capital of the firm, that is, knowledge of how to produce the latest corporate knowledge becomes a critical factor in providing large-scale and continuous innovations and progressive social and economic development of a country, in general.” Almost all scientists performing research of resources for the development of new economy have determined that it updates knowledge development. Combining provisions of philosophy, psychology and management presented in various research works, we have formed the theoretical basis for studying the cognitive potential of an employee. The necessity of gradual introduction of a research component into the academic activity of higher school is substantiated. The characteristic of each stage is presented as for the following: the purpose of the educational process, the criteria for assessing its results, the peculiarities of student's academic counselling.